Association of prenatal and childhood environment smoking exposure with puberty timing: a systematic review and meta-analysis - Yiwen Chen; Qin Liu; Wenyan Li; Xu Deng; Bo Yang; Xin Huang (Komiyama Printing Co. Ltd, 2018)
Abstract Objectives Mothers who smoke during pregnancy or while their children are small were common in some populations. Epidemiological studies have tried to detect the effect of prenatal tobacco smoke (PTS), and childhood environmental tobacco smoke (ETS) on puberty timing have not shown a consensus results. We aimed to examine current evidence and estimate the associations between PTS or/and ETS and puberty timing. Methods Seven databases were searched from inception to May 2017. All the cohort studies examining the associations between PTS and/or ETS and puberty timing were identified. Two reviewers independently screened all studies, evaluated the quality of eligible studies, and extracted the data. The quality assessment of the eligible cohort studies was based on the Newcastle-Ottawa Scale. Risk ratio (RR), standard mean difference (SMD), and 95% confidence intervals (CIs) were calculated and pooled by CMA (Version 2.0, Biostat, Inc., USA). Results Compared with controls, girls with PTS and ETS exposure have an earlier age at menarche (SMD − 0.087, 95% CI 0.174 to − 0.000), and similar results were found in both PTS subgroup (SMD − 0.097, 95% CI − 0.192 to − 0.002) and prospective cohort subgroup (SMD − 0.171, 95% CI − 0.253 to − 0.090). And number of boys with early voice break in PTS group was significantly increasing than non-exposed boys (RR 1.34, 95% CI 1.29 to 1.40). Conclusions PTS exposure possibly decrease age of menarche of girls, and studies on boys were urgent needed. Appropriate and comprehensive outcome measures using unified criteria to classify puberty should be reported in future studies.